2007
DOI: 10.4314/wsa.v31i3.5206
|View full text |Cite
|
Sign up to set email alerts
|

Improved sulphate removal rates at increased sulphide concentration in the sulphidogenic bioreactor

Abstract: The product of the biological sulphate reduction is sulphide. High concentrations of molecular H 2 S (g) can be inhibitory for microbial activity, especially at a reactor pH of 6 to 7. This paper focuses on the effect of high sulphide concentrations on the sulphate reduction rates. The results of three investigations operating a continuous reactor, a column reactor and batchtest reactors have shown that increased sulphide concentrations have resulted in improved biological sulphate reduction. In all instances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
5
6
0
Order By: Relevance
“…Sulfate-reducing bacteria (SRB) reduce sulfate (SO 4 2- ) to sulfide by transferring electrons obtained by the degradation of organic matter such as lactate and acetate. The presence of SRB decreases the final biogas production by competing with methanogen for acetate and by generating toxic H 2 S 58 . Values higher than 500 ppmv of sulfide in the biogas, produce a dangerous corrosive effect, significantly reducing the lifetime of pipes and other metallic hardware 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Sulfate-reducing bacteria (SRB) reduce sulfate (SO 4 2- ) to sulfide by transferring electrons obtained by the degradation of organic matter such as lactate and acetate. The presence of SRB decreases the final biogas production by competing with methanogen for acetate and by generating toxic H 2 S 58 . Values higher than 500 ppmv of sulfide in the biogas, produce a dangerous corrosive effect, significantly reducing the lifetime of pipes and other metallic hardware 9 .…”
Section: Introductionmentioning
confidence: 99%
“…From the above studies, it is evident that there are difficulties involved when setting sulphide concentrations so no inhibition of the anaerobic process occurs, however, there is a general consensus that anaerobic inhibition begins to occur at values of 50-250 mg sulphur/L. Although, there have been studies that not only obtain good performances from anaerobic reactors operating at higher concentrations than those identified above (Iza et al 1986), but it has also been suggested that increased concentrations of sulphur can enhance the biological sulfate reduction (Greben et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Besides NaHCO 3 , other types of alkalinity might also improve the SRE. Greben et al (2005) found that the addition of sulfide to the influent had a positive effect on sulfate removal, and resulted in improved biological sulfate reduction. Hence, in the acidogenic sulfidogenic system, the functional microbes, especially the SRB, favored higher alkalinity regardless of type.…”
Section: Resultsmentioning
confidence: 97%
“…In addition to neutralizing the acid generated by the biochemical process, carbonate alkalinity might be necessary to meet the inorganic carbon requirement of ammonia-oxidizer (Biesterfeld et al, 2003). Greben et al (2005) even found that addition of sulfide to the feed water had a positive effect on sulfate removal; however, excessive alkalinity negatively affected process performance. This fact was confirmed by Majumder and Gupta (2009) in anaerobic-aerobic reactor systems containing chlorophenols, where an alkalinity/ COD ratio in the influent of >1.1 caused gradual decrease in the chlorophenol removal in UASB reactors.…”
Section: Introductionmentioning
confidence: 97%